Historical Sources for Nahj Al-Balagha - Nurullayev, Fuad (Scholarya Demo Journal of Ruby, 2019)
One of the great personalities in the Islamic tradition is Imam Ali. He was an army commander, head of the state and was well-known for his knowledge, intelligence and services to Islam. Being one of the early followers of Islam, he mastered the subtleties and spirit of the religion. Whether as a leader or a person in his relation to others, he adhered to the principles of the religion and acted accordingly. Ali (pbuh) grew up close to the Prophet (pbuh) since his childhood, and benefited from his education and intelligence. This knowledge was reflected in the sermons, hadiths, and letters of Hazrat Ali. The words, sermons, and letters that belonged to him were collected over twenty years by the well-known thinker and writer Seyyid Razi (359 / 970-406 / 1015) and introduced with the work called Nahj-al-Balagha. This work covers 241 sermons, 79 letters and 480 short stories by Hazrat Ali. According to some researchers, it is possible that some of the sermons and sayings in Nahj-al-Balagha might not belong to Hazrat Ali. Some researchers think it is doubtful the sayings in the book belonged to Hazrat Ali. However, it should be noted that the philosophical-social ideas in the work, as well as its expression and style, indicate that the work is the product of the intelligence of Hazrat Ali. At the same time, the sources which narrate the stories of the work reveal that the author is Hazrat Ali. The article investigates the sources about Nahj-al-Balagha and define itsrelation to Hazrat Ali.